Path Analysis Between Shoot Dry Weight And Its Contributing Characters in Seedlings of Pinus roxburghii Sargent - Kumar, Ranjeet; Gupta, H. K.; Chauhan, K. C. (Indian Journal of Agroforestry, 2020)
Data for traits i.e. seed length, seed width, 100- seed weight were recorded in the laboratory for 42 seed sources of Pinus roxburghii. Field germination, seedling height, collar diameter, needle length and dry shoot weight were observed in the fields for six month seedlings. The effects of various traits viz., 100 seed weight (0.507) followed by needle length (0.456), seedling height (0.422), and collar diameter (0.140) on dry weight were positive. Path analysis revealed that characters viz., seedling height, collar diameter, needle length and 100 seed weight had positive and direct effect on dry shoot weight indicating their direct involvement and relative importance for increasing the biomass.